2021
DOI: 10.3390/biom11091285
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Peptides to Protect Ferulic Acid against Ultraviolet Radiation Based on Domain Site IIA of Bovine Serum Albumin

Abstract: Ferulic acid (FA) is known for its excellent antioxidant properties, which can provide many health benefits. One of its drawbacks is its instability under UVA light, which limits its potency. In this study, the new peptides LW2 (QNKRFYFRKNQ) and CW2 (a cyclic form of LW2) were designed based on bovine serum albumin site IIA conformation. A UVA irradiation experiment was performed to investigate the protective ability of these peptides towards FA against UVA damage. The percentages of FA remaining under UV irra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…CW2 could protect FA, showing a reservation ratio of 83% after 12 h of exposure to UVA. As shown in Figure 3, the cationic and hydrophobic moieties of CW2 were essential to enhance the electrostatic and hydrophobic interactions with FA, respectively [43]. The authors suggested that the presence of the rigid cyclic structure is important to protect FA against destructive effects of UVA.…”
Section: Abps As Protective Shields For Sensitive Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…CW2 could protect FA, showing a reservation ratio of 83% after 12 h of exposure to UVA. As shown in Figure 3, the cationic and hydrophobic moieties of CW2 were essential to enhance the electrostatic and hydrophobic interactions with FA, respectively [43]. The authors suggested that the presence of the rigid cyclic structure is important to protect FA against destructive effects of UVA.…”
Section: Abps As Protective Shields For Sensitive Bioactive Compoundsmentioning
confidence: 99%
“…The authors also estimated the importance of the positively charged Arginine amino acid computationally using Molecular Operating Environment MOE 2018.0 software (Chemical Computing Group, Canada). The computational simulation of the minimized structure of CW2 demonstrated the great role of arginine in initiating electrostatic interaction with FA [43].…”
Section: Abps As Protective Shields For Sensitive Bioactive Compoundsmentioning
confidence: 99%